EVALUATION STRUCTURAL CONDITIONS AND REMAINING LIFE OF RIGID PAVEMENT (CASE STUDY: NATIONAL ROADS BATANG-BATAS KENDAL) - Paus, Made
Structural damage is a defect that causes a pavement can’t serve the existing traffic load. The purpose of this research is to evaluate the performance of existing rigid pavement (structural evaluation) and the maintenance (additional layer) needed to increase the rigid pavement structural value and to know the remaining pavement service life period by using the AASHTO 1993 method. Structural evaluation in the AASHTO 1993 method are using two (2) comparison methods to determine the required thickness of additional layer, the comparison is based on a road condition survey and based on service life (remaining life). Road condition survey conducted to inventory the damage of road pavement in the field, while the evaluation based on remaining life is viewed in terms of road design that the past load in the road lane is according to the design, considering the improvement of traffic conditions from year to year. The overlay design is using deflection data FWD (Falling Weight deflectometer) as an data input in the 1993 AASHTO method. Backcalculation process was performed to determine the value of Modulus of Elasticity of the concrete pavement. Traffic data is used to determine the value of service life and the additional layer thickness (overlay) of concrete pavement. The study results show that the theoretical value of Modulus of Elasticity Concrete in first segment is below 3 million psi, where the concrete pavement damage is severe enough, it can be compared with the results of field surveys. The additional layer thickness results based on road condition survey for second segment is 16,00 cm and for third segment is 8,00 cm, while additional layer thickness results based on remaining life for second segment is 13,00 cm and for third segment is 10,00 cm. The service life of concrete pavement results is 73,24% for second segment and 82,80% for the third segment. The significant difference of additional layer thickness for each segment are generated based on a road condition survey.